Living Sola Fide: Features of Religious Recognition. (2nd September 2013) - Saarinen, Risto
Abstract: This article discusses the life of faith and forensic justification as related to some new issues in social theory, especially Axel Honneth's notions of love, respect, and esteem. The article is critical of virtue ethics and recommends an ethics of vocation as a path toward equal respect and individual social esteem. The article also discusses why Lutherans consider faith (or even faith alone) rather than love as a proper starting‐point of this path.